The role of the ERP system in the rapid increase of production - Josip Nađ (Trends in Computer Science and Information Technology - Peertechz Publications, 2022)
ERP systems can play a crucial role in the company's ability to adapt to new situations and unexpected changes. This paper deals with the example of a company that unexpectedly, after several years of stagnation, got the opportunity to double its production. The main challenge was not only the increase in production but also the additional requirements for the traceability of individual packages of raw materials and individual packages of finished products. An additional request was a completely different method of product costing and production order settlement than previously used. The management reacted quickly and took all the necessary steps to adjust the existing production lines and the existing ERP system to the new requirements. While local managers took care of the adjustment of production lines, an experienced SAP consultant was hired to work on the necessary adjustments to the ERP system and design the interface with external systems. He took over all communication with developers of external systems. A central project team was formed, which decided on the way in which the change of all parts of the ERP system will take place, primarily in terms of the time planning of the necessary actions. The plan was completely successful. In just 5 months, the production lines were technically adjusted and prepared for the new production method. At the same time, the ERP system was completely revised and supplemented with requested new functionalities, including the creation of all necessary interfaces with external systems for scanning individual packages. The management's final assessment is that this would not have been possible without first having a fast and robust ERP system.